Penerapan Metode Eoq Untuk Efisiensi Biaya Pada Produk Headlining Di Perusahaan Komponen Otomotif PT. Y - Dzulfikar, Arif; Setianingsih, Putri; Sitorus, Marison; Jatmiko Nuryatno, Yulius; Sundoro, Dionisius (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
PT.Y is a national automotive component company, where one of its products is Headlining Assy Roof which is routinely distributed to automotive manufacturing companies in Indonesia. The problem which occurs is high frequent orders cause high ordering costs and high storage costs, not meeting the company's targets. Therefore, this study aims to determine the optimal and economical number of raw material orders, reorder time or reorder point, safety stock, and the amount of total inventory cost; so that raw material inventory control gets optimal results to support smooth production. This research is a descriptive study with a quantitative approach, data collection techniques based on the company's historical data related to ordering and storage costs. The analysis method uses the Economic Order Quantity (EOQ) by applying mathematical formulas. With the EOQ formula, the company can identify the most cost-effective order quantity, Headlining Assy Roof. The results of the study show that with the Economic Order Quantity (EOQ) method, the optimal order quantity is 679,248 pcs, with an order frequency of 8 times/ year, an ordering cost of Rp 5,125,167/ year, a storage cost of Rp 5,124,773/ year, and a total inventory cost (TIC) of Rp 10,249,940/ year. With the EOQ method, the total savings in TIC inventory costs that can be obtained by PT. Y is Rp 132,870,060/ year compared to the company's previous method.